Improving Teachers' Capabilities in the Using of the Teaching Aids (Props) Through Academic Supervision at Gema Bukit Barisan Private SMP, Tanjung Morawa District - Tina; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
Improving the ability of teachers in making teaching aids through academic supervision at the private junior high school, Gema Bukit Barisan, Tanjung Morawa sub-district. In the educational philosophy of Ki Hajar Dewantara, Ing Ngarso Sung Tulodo, Ing Madya Mangun Karso, Tut Wuri Handayani, it means that learning is student-centered. However, until now, the learning that takes place in the research-assisted schools is more teacher-centered. This is because the teacher still does not want to take the time to make teaching preparations. The time of the research is carried out in semester 1 of the 2021/2022 academic year starting the first week of October and ending in the fourth week of December. The research was carried out in one of the schools that was supervised by the supervisor, namely the Gema Bukit Barisan Private Junior High School Tanjung Morawa. Indicators of success in this study are (1) increasing the ability of teachers in making teaching aids, (2) increasing student motivation in learning. From the supervision I did to the three teachers at the private SMP, Gema Bukit Barisan, Tanjung Morawa District, they have begun to understand how important it is to make teaching aids in learning activities in the classroom. Previously, they had never made or used teaching aids. With my direction and guidance, they understand and can use it according to the subject or material that is understood.